Nephrotic syndrome secondary to alpha-1 antitrypsin deficiency. Issue 3 (5th March 2021) - Santos, Gabriela F; Ellis, Paul; Farrugia, Daniela; Turner, Alice M
Abstract : We report a 64-year-old caucasian woman diagnosed with membranous nephropathy secondary to alpha-1 antitrypsin deficiency (AATD). AATD is a rare autosomal codominant genetic disorder. Its clinical manifestations are mostly observed in the lungs, with early-onset emphysema. Nephropathy due to AATD is still very rare and only a few cohort studies have been reported. It has been recognised that alpha-1 antitrypsin has a protective role in the kidneys which enhances the possibility of development of kidney failure, such as nephrotic syndrome, in cases of AATD. Further clinical investigation is needed to understand the relationship between the development of nephropathy, namely membranous nephropathy, and AATD.